2014
DOI: 10.1021/nn502065u
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Semitransparent Conductive Hybrid Hydrogels for Flexible Supercapacitors

Abstract: Conductive polymers showing stretchable and transparent properties have received extensive attention due to their enormous potential in flexible electronic devices. Here, we demonstrate a facile and smart strategy for the preparation of structurally stretchable, electrically conductive, and optically semitransparent polyaniline-containing hybrid hydrogel networks as electrode, which show high-performances in supercapacitor application. Remarkably, the stability can extend up to 35,000 cycles at a high current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(128 citation statements)
references
References 47 publications
(88 reference statements)
3
125
0
Order By: Relevance
“…Hao et al [36] reported a highly flexible PANI-containing conductive hydrogel based on preorganized α-cyclodextrins polyacrylamide (α-CD-PAAm) host hydrogels. Firstly, the host α-CD-PAAm hydrogel was prepared through a sol gel process, which contained amphiphilic domains that allowed aniline (ANI) molecules gathering in the nonpolar cavities of α-CD.…”
Section: Conducting Polymer Hydrogel Flexible Electrodes and Supercapmentioning
confidence: 99%
“…Hao et al [36] reported a highly flexible PANI-containing conductive hydrogel based on preorganized α-cyclodextrins polyacrylamide (α-CD-PAAm) host hydrogels. Firstly, the host α-CD-PAAm hydrogel was prepared through a sol gel process, which contained amphiphilic domains that allowed aniline (ANI) molecules gathering in the nonpolar cavities of α-CD.…”
Section: Conducting Polymer Hydrogel Flexible Electrodes and Supercapmentioning
confidence: 99%
“…Among various functional hydrogels 911 , conductive hydrogels are very promising as stretchable conductive materials, which have been extensively studied for applications such as stretchable sensors 7,8,12 and supercapacitors 13,14 . Most of the conductive hydrogels are made into two-dimensional films or three-dimensional monoliths by molding methods 15,16 , which result in an amorphous material with polymer chain’s random orientation and disordered alignment.…”
Section: Introductionmentioning
confidence: 99%
“…5d, various transparent soft materials were compared in terms of their strength and elasticity [53]. Hydrogels constitute another type of transparent soft films [54][55][56]. However, different from the mechanically tough PDMS, the hydrogels are usually mechanically weak owing to their "wet" components (hygrophilic gel).…”
Section: Resultsmentioning
confidence: 99%